Systematic review of physical activity and cognitive development in early childhood. Issue 7 (July 2016) - Carson, Valerie; Hunter, Stephen; Kuzik, Nicholas; Wiebe, Sandra A.; Spence, John C.; Friedman, Alinda; Tremblay, Mark S.; Slater, Linda; Hinkley, Trina
Abstract: Objectives: To comprehensively review all observational and experimental studies examining the relationship between physical activity and cognitive development during early childhood (birth to 5 years). Design: Systematic review. Methods: Electronic databases were searched in July, 2014. No study design, date, or language limits were imposed on the search. Included studies had to be published, peer reviewed articles that satisfied the a priori determined population (apparently healthy children aged birth to 5 years), intervention (duration, intensity, frequency, or patterns of physical activity), comparator (various durations, intensity, or patterns of physical activity), and outcome (cognitive development) study criteria. Study quality and risk of bias were assessed in December 2014. Results: A total of seven studies, representing 414 participants from five different countries met the inclusion criteria, including two observational and five experimental studies. Six studies found increased or higher duration/frequency of physical activity had statistically significant ( p < 0.05) beneficial effects on at least one cognitive development outcome, including 67% of the outcomes assessed in the executive function domain and 60% in the language domain. No study found that increased or higher duration/frequency of physical activity had statistically significant detrimental effects on cognitive development. Six of the seven studies were rated weak quality with a high risk of bias. Conclusions: This review provides some preliminary evidence that physical activity may have beneficial effects on cognitive development during early childhood. Given the shortage of the information and the weak quality of available evidence, future research is needed to strengthen the evidence base in this area.